2005
DOI: 10.1007/s11224-005-4445-x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Normal to Strong Hydrogen Bonds

Abstract: We review our theoretical work done on a variety of different chemical systems, which show different H-bonding characteristics. The systems include water clusters, its interactions with polar molecules and π -systems, organic nanotubes, enzymes, and ionophores/receptors. Special features of normal, short, short strong, and π -type H-bonding interactions in these systems are discussed in terms of structures, interaction energies, and spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 140 publications
1
35
0
1
Order By: Relevance
“…Stärkere Brücken haben einen zunehmend kovalenten Charakter und tendieren zu mehr kooperativen Effekten durch gegenseitige Polarisierung der Gruppen. [320] In schwächeren Komplexen dominiert der elektrostatische Anteil, auch in vielen Brücken mit ionischen Partnern. [321] Dadurch erklärt sich die relative große Toleranzbreite des Zusammenhangs zwischen Bindungsstär-ke und Geometrie der D···H···A-Anordnung.…”
Section: Grundlagenunclassified
“…Stärkere Brücken haben einen zunehmend kovalenten Charakter und tendieren zu mehr kooperativen Effekten durch gegenseitige Polarisierung der Gruppen. [320] In schwächeren Komplexen dominiert der elektrostatische Anteil, auch in vielen Brücken mit ionischen Partnern. [321] Dadurch erklärt sich die relative große Toleranzbreite des Zusammenhangs zwischen Bindungsstär-ke und Geometrie der D···H···A-Anordnung.…”
Section: Grundlagenunclassified
“…In the review by Pak et al [75], theoretical results are reported for many different chemical systems (gas phase water clusters, organic nanotubes, enzymes, and receptors), which exhibit wide variety of different hydrogen bonding characteristics such as normal, short, short strong, and p-type hydrogen bonds. The use of ab initio calculations is summarized.…”
Section: Issuementioning
confidence: 99%
“…Quantum chemical calculations can be used to characterize hydrogen bonds in many ways beyond the experimental possibilities. A comprehensive work published in Structural Chemistry involving theoretical investigation of hydrogen bonding was reported by Pak et al [47]. Their review included numerous chemical systems showing normal to strong hydrogen bonds: water clusters, interaction of water with polar molecules and psystems, interactions in organic nanotubes, enzyme catalysis, and host-guest interactions.…”
Section: Theoretical Studiesmentioning
confidence: 99%